Canon of the five orders of architecture - Vignola, giacomo barozzi 1507-1573.; Leeke, John.; Watkin, David, 1941- (Mineola, N.Y. : Dover Publications, Inc., 2011)
One of history's most published architectural treatises, this Renaissance volume solidified the architectural canon of the past five centuries. In these pages, the distinguished architect known as Vignola identified the five orders - Tuscan, Doric, Ionic, Corinthian, and Composite - and illustrated them in full-page elevational detail. Vignola's engravings have been copied countless times since their original publication in 1562. The clear images with brief captions constitute a practical rather than theoretical work, offering even lay readers a system of tools that provide accurate proportions. An essential reference for professional architects, this book has guided generations of architects, including those who rebuilt London after the Fire of 1664. This new edition features an Introduction by architectural historian David Watkin.
Cover Page; Title Page; Copyright Page; Introduction; To the Reader; The Translators Preface; Back Cover.
"This Dover edition, first published in 2010, is an unabridged republication of The Regular Architect: or the General Rule of the Five Orders of Architecture, printed for William Sherwin, London, in 1669."
Keywords: Architecture -- Orders